Health literacy, emotionality, scientific evidence: Elements of an effective communication in public health - Luigi Roberto Biasio; Annalaura Carducci; Gaetano Maria Fara; Giuseppe Giammanco; Pier Luigi Lopalco (Taylor & Francis Group, 2018)
The importance of healthcare providers' communication abilities is still underestimated. Informing the population on the basis of documented evidence is essential but not enough to induce a change in the beliefs of who is doubtful or does not accept preventive interventions, such as vaccination. Lining up the offer of prevention to the knowledge of the citizens, also improving Health Literacy skills, is a critical step toward their empowerment and behavior change. The 2017 Erice Declaration was drafted to propose to the Institutions and the scientific community the main goals to improve communication and counteract Vaccine Hesitancy, at a very critical time, when mandatory vaccination was introduced in Italy.